Mandatory Disclosure and Individual Investors: Evidence From the Jobs Act - Colleen Honigsberg; Robert J. Jackson Jr.; Yu-Ting Forester Wong (Washington University Law Review, 2015)
One prominent justification for the mandatory disclosure rules that define modern securities law is that these rules encourage individual investors to participate in stock markets. Mandatory disclosure, the theory goes, gives individual investors access to information that puts them on a more equal playing field with sophisticated institutional shareholders. Although this reasoning has long been cited by regulators and commentators as a basis for mandating disclosure, recent work has questioned its validity. In particular, recent studies contend that individual investors are overwhelmed by the amount of information required to be disclosed under current law, and thus they cannot—and do not—use that information to analyze the companies that they own. Using a recent change in the law that allows firms to disclose less information before their initial public offering (“IPO”), we examine whether reduced disclosure leads to less trading by individual investors. Our results show that, immediately following the IPO, individual investors are less likely to trade in the stocks of the firms that provide less disclosure—but that this difference disappears after two weeks of trading. Our findings have important implications for the lawmakers now examining whether, and how, to change the mandatory disclosure rules that have served as the basis of federal securities law for generations.
Keywords: Jobs Act; Corporate Law; Mandatory disclosure; Securities Law; IPO